Macromolecular modifications of poly(etherketoneketone) (PEKK) copolymer at the melting state. (September 2018) - Choupin, T.; Fayolle, B.; Régnier, G.; Paris, C.; Cinquin, J.; Brulé, B.
Abstract: Macromolecular modifications of poly(etherketoneketone) (PEKK) copolymer prepared from diphenyl ether (DPE), terephthalic acid (T) and isophthalic acid (I) with a T/I ratio of 60/40 have been investigated above its melting temperature by gel permeation chromatography (GPC), differential scanning calorimetry (DSC) and rheological measurements to assess the evolution of PEKK matrix during composite consolidation step. We mainly focused in this study on anaerobic conditions, i.e. degradation under nitrogen or in lack of oxygen. During exposure, thermal degradation leads to an increase of weight average molar mass Mw and viscosity which is typical to crosslinking/branching mechanism as already observed for PEEK in the literature. However, thanks to GPC measurements, it appears that a chain scission mechanism occurs in the same time related to a constant number average molar mass Mn . Crosslinking kinetics are identified at several temperatures between 320 and 400 °C with rheological measurements from a kinetic scheme governing the crosslinking mechanism. At last, the influence of the crosslinking process on PEKK crystallization is investigated. The final crystallinity and crystallization kinetics decrease with crosslinking due to branching of macromolecular chains. Highlights: Anaerobic degradation of PEKK results in crosslinking and chain scission processes. Crosslinking vs chain scission is characterized by molar mass and viscosity. Crosslinking is predominant over chain scission. Final crystallinity and crystallization kinetics decrease with degradation time.